Sequential hydrozirconation/Pd-catalyzed cross coupling of acyl chlorides towards conjugated (2E,4E)-dienones - Kolb, Benedikt; Silva dos Santos, Daniela; Krause, Sanja; Zens, Anna; Laschat, Sabine (Beilstein Journal of Organic Chemistry, 2023)
Dienones are challenging building blocks in natural product synthesis due to their high reactivity and complex synthesis. Based on previous work and own initial results, a new stereospecific sequential hydrozirconation/Pd-catalyzed acylation of enynes with acyl chlorides towards conjugated (2E,4E)-dienones is reported. We investigated a number of substrates with different alkyl and aryl substituents in the one-pot reaction and showed that regardless of the substitution pattern, the reactions lead to the stereoselective formation (≥95% (2E,4E)) of the respective dienones under mild conditions. It was found that enynes with alkyl chains gave higher yields than the corresponding aryl-substituted analogues, whereas the variation of the acyl chlorides did not affect the reaction significantly. The synthetic application is demonstrated by formation of non-natural and natural dienone-containing terpenes such as β-ionone which was available in 4 steps and 6% overall yield.
Keywords: cross coupling; hydrozirconation; palladium catalysis; Schwartz's reagent; terpenes